Bооm and crisis of «dot-сoms» in the USA (1995–2000) - Мошенський, Сергій Захарович (Problems of Theory and Methodology of Accounting, Control and Analysis, 2018)
Financial crises are always predated by periods of prolonged economic recovery and the speculative boom around the stock of certain innovative companies. When the lift reaches its climax, and the market prices of the shares are maximally inflated, a quick decline and crisis begin. "Dot-com" boom (companies that have engaged in sales of goods and services via the Internet) was preceded by a long economic upswing of the 1990s, one of the largest lifts of the twentieth century. Information technology was at the forefront of it, especially the mass proliferation of the Internet since the mid- 1990s. A large number of new Internet companies appears, the majority of which wanted to receive money from the issue of shares, regardless of whether a business of selling goods and services via the Internet would be profitable. As is the case with all joint-stock boom that took place earlier, this approach led to the "dot-com" crisis of March 10, 2000. On the NASDAQ stock market, where most of the «dot-com» shares traded, a rapid drop in their rates began. The huge losses are evidenced by the fact that during 2000, the NASDAQ index fell almost 50 %. If there were over three hundred «dot-coms» in 1999, in 2001, only 76 left. The total capitalization of the «dot-com» shares, part of the Bloomberg US Internet index, fell after the crisis by 1,755 trillion dollars, and the market prices of most stocks declined in 2000 by 80–90 %. Due to the speed of the fall in stock prices, the "dot-com" crisis can be compared with the «Great crash» of 1929. Although the crisis was short-lived and two years later it was replaced by a new rise, the «dot-com» crisis began the sequence of events that led to large-scale global crisis of 2007–2009. Nobody wanted to hinder the heated market of securities, so the «dotcoms» were superseded by the mortgage boom of the mid-2000s.